DIVERSITY OF ANTS (HYMENOPTERA: FORMICIDAE) IN RESIDENTIAL AREA OF TARBELA, SWABI: NEW RECORDS FROM PAKISTAN - S. B. Rasheed; M. Ali; F. Zaidi; S. Noreen (Journal of Animal and Plant Sciences, 2020)
Twenty-one species of ants, including nine new records from Pakistan were collected from residential colonies of Tarbela Power Station, Swabi. These species were classified into four subfamilies and thirteen genera. The most diverse genus was, Camponotus represented by four species i.e. Camponotusangusticollis Jerdon, 1851, Camponotus compressus Fabricius, 1787, Camponotusoblongus Forel, 1916, Camponotussericeus Fabricius, 1798. Three species of Pheidole i.e. Pheidole binghami Forel, 1902,Pheidole sykesi and Pheidole sagei Forel, 1902, and two species each of Monomorium and Lepisiota i.e. Monomoriumindicum Forel, 1902,Monomoriumsagei Forel, 1890 and Lepisiotafrauenfeldi Mayr, 1855, Lepisiotacapensis Mayr, 1862 were reported in current study. Remaining ten genera i.e. Crematogaster, Meranoplus, Messor, Cataglyphis, Cardiocondyla, Aenictus, Polyrachis, Paratrechina, Nylanderia and Tapinoma were represented by single species each; Crematogaster subnuda Mayr,1878, Messor semirufus Smith, 1858, Cataglypussetipes Forel, 1894, Meranoplusbicolor Guerin-Meneville,1844, Cardiocondyla mauritanica Forel, 1890, Aenictuswroughtonii Forel,1890, Polyrachis hauxwelli  Bingham, 1903,Paratrechinalongicornis Latreille, 1802, Nylanderiaindica (Forel, 1894) and Tapinomaindicum Forel (1895). The species first time recorded from Pakistan were Camponotus angusticollis, Lepisiota capensis,Messor semirufus, Pheidole sykesi, Monomorium sagei, Nylanderia indica and Tapinoma indicum.
Keywords: Diversity; Formicidae; New records; Pakistan; Swabi